Caught in the Middle: Intergenerational Caregiving Experiences Among Sandwich Generation Filipino Women - Suaco, Lara Angeli S.; Ancho, Inero V.; Dy, Marison Felicidad R.; Recto, Ferlynn B.; Pelegrina, Daisy V.; Albor, Rufo Gil Z.; Almeda, Phrygian P.; Sagun, Danica Jae B. (Bina Nusantara University, 2025)
Despite the prevalence of sandwich generation Filipino women in the Philippines, their nuanced and unique experiences of being caught in the middle of two or more generations remain an understudied social phenomenon. The present study is a phenomenological research study that aimed to investigate the lived experiences of sandwich generation Filipino women and how they made sense of their circumstances amid the backdrop of intergenerational caregiving and the associated burden they carry. The study utilized purposive sampling in gathering eight sandwich generation Filipino women participants living in Metro Manila, who were later interviewed through one-on-one, in-depth interviews. Data was then transcribed and analyzed through thematic analysis; wherein significant themes were generated to produce meaningful narratives depicting intergenerational caregiving among sandwich generation Filipino women. Specifically, the findings of the study revealed that these women assume the primary caregiver role and fulfill domestic along with economic responsibilities due to a perceived sense of responsibility to pay back or help their families coupled with gender roles and norms. It is a deliberate choice that they make daily as they go through both rewarding and challenging experiences. In moving forward, they aspire for the future generation to have more agency and autonomy over their lives. The study shed light on the struggles of sandwich generation Filipino women, hence providing information on how different entities can pave the way for the increased visibility of unpaid care work and upholding Filipino women’s full rights.